2018
DOI: 10.1038/s41591-018-0049-z
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR–Cas9 genome editing induces a p53-mediated DNA damage response

Abstract: Here, we report that genome editing by CRISPR-Cas9 induces a p53-mediated DNA damage response and cell cycle arrest in immortalized human retinal pigment epithelial cells, leading to a selection against cells with a functional p53 pathway. Inhibition of p53 prevents the damage response and increases the rate of homologous recombination from a donor template. These results suggest that p53 inhibition may improve the efficiency of genome editing of untransformed cells and that p53 function should be monitored wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
728
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 973 publications
(758 citation statements)
references
References 19 publications
22
728
2
6
Order By: Relevance
“…Like other genome engineering approaches, CRISPR-Cas systems also have potential ethical concerns and safety issues [57]. In this study, we reported that the widely-used Cas9 nuclease can cause a STING-STAT6-dependent innate response in human cells (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Like other genome engineering approaches, CRISPR-Cas systems also have potential ethical concerns and safety issues [57]. In this study, we reported that the widely-used Cas9 nuclease can cause a STING-STAT6-dependent innate response in human cells (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The CRISPR-Cas9 system could correct the genetic errors that cause human disease; this has culminated in the initiation of early-phase clinical trials. In addition to ethical concerns raised by human genome editing, major safety issues identified from these clinical studies include increased cancer risks, off-target effects, and unwanted host immune responses [57]. However, the direct impact of exogenous Cas9 protein on human immune cells remains unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are safety concerns associated with doublestrand breaks (DSBs) induced by genome-editing tools. DSBs are known to cause activation of the tumor-suppressor protein p53, resulting in reduced insertion efficiency of target genes because of cell-cycle arrest or apoptosis (Haapaniemi et al 2018;Ihry et al 2018); moreover, multiple DSBs may cause large deletions (Kosicki et al 2018) or translocations (Qasim et al 2017) of DNA. In addition to improvements in CAR-T therapy, ongoing research seeks to develop novel anticancer cell therapies by introducing CAR genes into various adaptive and innate immune effector cells, such as natural killer (NK) cells, natural killer T (NKT) cells, gamma-delta T (cdT cells), and phagocytic macrophages (Morrissey et al 2018;Saudemont et al 2018).…”
Section: Considerations For Improving Car-t Therapymentioning
confidence: 99%
“…Two additional and significant safety concerns are directly linked to the induction of DSBs for genome editing by RGNs and could altogether be prevented by approaches that act independent of DSBs, such as base editing and transcriptional or posttranscriptional regulation. First, effective DSB induction may lead to P53-dependent apoptosis, and recent independent studies have pointed out that selecting for DSB-dependent editing events may thus select for P53-deficient cells and cell populations with elevated cancer risk [155157]. Such enrichment may be prevented by suppressing P53 activity at the time of editing, and it remains to be shown whether the observations for both studies can be reproduced in clinically relevant cell types.…”
Section: Room For Improvementmentioning
confidence: 99%